Guillaume Houppelande’s Small Treatise on the Immortality of the Soul - Matula, Jozef (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2023)
This article focuses on the treatise De immortalitate animae (Paris, 1491) written by Guillaume Houppelande, one of the most famous members of the Faculty of Theology of the University of Paris in the fifteenth century. Houppelande’s treatise, which refers to ancient, patristic, and medieval sources, contains several arguments on the immortality of the soul. Special attention is first given to Houppelande’s attitude towards those philosophical and theological theories that supported his own arguments before focus is turned towards an analysis of Houppelande’s relationship to medieval philosophy.